The changing faces of populism: systemic challengers in Europe and the US (Brussels, 2013)
"This book was born out of a joint conference of the three foundations involved. It offers a selection of case studies to reflect the diversity and wide spectrum of populist movements that presently exist in Europe and North America. It provides a snapshot of groups ranging from new street movements and quasi-parliamentary organisations to those that have been somewhat systematised. Populism is both a reaction to, and a product of, the growing distance between citizens and their institutions of governance, whether that is at state or European level. This publication represents an effort to further understand these movements – and the conditions that allow for their growth – through rigorous, multidisciplinary research and empirical analysis. The variety of interpretations contained in this book points to the intractability and complexity of this issue. FEPS, Italianieuropei and CRS hope that this contribution will be a useful reference point for readers and will contribute to better political understanding and democratic consolidation."